Development of a Nanoemulgel for the Topical Application of Mupirocin - Bahjat Alhasso; Muhammad Usman Ghori; Simon P. Rout; Barbara R. Conway (Pharmaceutics, 2023)
Mupirocin (MUP) is an effective topical antibiotic with poor skin permeability; however, its skin permeability can be improved by a nanoemulsion formulation based on eucalyptus oil or eucalyptol. Despite this improvement, the nanoemulsion has limitations, such as low viscosity, low spreadability, and poor retention on the skin. To overcome these limitations, the aim of this study was to develop a nanoemulgel formulation that would enhance its rheological behaviour and physicochemical properties. The MUP nanoemulgel was prepared by incorporating a preprepared MUP nanoemulsion into Carbopol gel at a concentration of 0.75% in a 1:1 ratio. The nanoemulgel formulations were characterised and evaluated for their physicochemical and mechanical strength properties, rheological behaviour, and in vitro skin permeation and deposition, as well as antibacterial studies. Both nanoemulgels exhibited stability at temperatures of 4 and 25 °C for a period of 3 months. They had a smooth, homogenous, and consistent appearance and displayed non-Newtonian pseudoplastic behaviour, with differences in their viscosity and spreadability. However, both nanoemulgels exhibited lower skin permeability compared to the marketed control. The local accumulation efficiency of MUP from nanoemulgel after 8 h was significantly higher than that of the control, although there was no significant difference after 24 h. Micro-CT scan imaging allowed visualisation of these findings and interpretation of the deposited drug spots within the layers of treated skin. While there were no significant differences in the antibacterial activities between the nanoemulgels and the control, the nanoemulgels demonstrated superiority over the control due to their lower content of MUP. These findings support the potential use of the nanoemulgel for targeting skin lesions where high skin deposition and low permeability are required, such as in the case of topical antibacterial agents.